PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN MEBEL ALUMINIUM DI DESA SUNGAI DURAIT TENGAH KECAMATAN BABIRIK KABUPATEN HULU SUNGAI UTARA (STUDI KASUS PADA BAPAK YANUR) - Hasanah, Nurul; Jainah, Jainah (PPPM STIA Amuntai, 2022)
This study was conducted to examine the effect of product quality on consumer buying interest which is motivated by the fact that along with the development of the times, many people like aluminum furniture products. And to find out and analyze the effect of product quality on consumer buying interest in aluminum furniture. This study used 35 respondents as the research sample and the sample collection technique was the census technique. If the population is less than 100, it is better if the entire population is used. The data analysis method used is quantitative analysis which includes validity test, reliability test, simple regression test, test determinasr (r2), and T test. The tested data was then processed with SPSS software version 25, of all the statements are said to be valid. It can be stated that the value of rcount > rtable. For reliability test if Cronbach alpha > 0.60 for product quality variable there are 15 statements and for buying interest variable there are 8 statements, product quality (0.951 > 0.60) and buying interest (0.953 > 0.60). Simple Linear Regression, the regression coefficient for a constant of -6.210 indicates that the quality variable is zero or fixed, it will increase buying interest by -6.21 units or by 6.21%. The product quality variable shows that 0.597 if the unit increases it will increase buying interest by 0.597 or 59.7%. The coefficient of determination r2 is known to be rquare of 0.810 or 81%, indicating that product quality has an influence on the buying interest variable of 81%. And the hypothesis test (T test) tcount > ttable (11.850 > 2.034) it can be concluded that product quality has a significant effect on buying interest. Maintaining product quality in the community so that people are interested in buying products because of good quality and product designs that attract interest in buying them.